CURRICULUM REDESIGN OF SHARIA ECONOMIC THROUGH INTEGRATION OF SCIENCE TOWARDS INDEPENDENT LEARNING AND INDEPENDENT CAMPUS AT THE STATE ISLAMIC UNIVERSITY OF SULTAN MAULANA HASANUDDIN BANTEN - Hadi Peristiwo (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2020)
Higher education curriculum terms of reference are absolutely necessary to develop science and prevent unequal quality of graduates. Curriculum courses Islamic economics are integrated is the curriculum that evolves to adjust to the needs of the times will however still be guided by the moral message of Islam. The main objective of this research is to explore the redesign of the sharia economic curriculum during the establishment of policies for independent learning and independent campuses and to find out the appropriate Islamic economic curriculum design that can be applied during the policy era for independent learning and independent campus. This research uses a qualitative approach. The method used in this research is descriptive analysis. Sources of data in this study come from books, journals and interviews with informants related to the preparation of the Islamic economic curriculum at several universities related to the policy of independent learning-independent campus. From the results of the study can be obtained conclusion that the program policy of independent learning and campus independence is a simplification effort to accelerate the achievement of a competitive college. Higher education through study programs is expected to realize an increase in the quality of learning programs in providing education, especially in the sharia economic economics which is in the State Islamic University of Sultan Maulana Hasanuddin Banten.